Potential climate change impacts on water resources in Jammu - RASHID, GULSHAN; KHUSHU, M. K.; RAZA, NAZIA; SINGH, MAHENDER; KHAR, SANJAY (Journal of Soil and Water Conservation, 2020)
While studying the climatic change scenario of Jammu region, it was revealed that during the period between 1985 and 1995, the rise in temperature in Jammu district was 0.046°C per year, while as during the period from 1996 to 2004 the temperature increase was found to be 0.155°C per year. If the trend persists in similar manner, the temperature would rise above 3°C in another 20 years. The rise in temperature will have a profound effect on crop water demand and ultimately water resources. Crop water demand was determined under different temperature scenario with the help of FAO CROPWAT model, window version 4.2 (FAO, 1995) assuming other meteorological parameters as normal. The investigation revealed that with an increase in annual mean temperature by 0.5°C, the crop water demand increases by 1.1% and it may go as high as 7.8% if the temperature rose by 3°C.